MORPHOLOGICAL CHANGES IN TOOTH DENTIN AT VARIOUS STAGES OF ABRASION AND THEIR IMPACT ON THE CHOICE OF ORTHOPEDIC TREATMENT - Mykola M. Maliuchenko; Petro A. Hasiuk; Anna B. Vorobets; Tetiana I. Dzetsiukh; Dmytro D. Kindiy; Iuriy A. Gasiuk; Pavlo M. Maliuchenko (Клінічна та профілактична медицина)
Introduction. The severity of orthopedic treatment of patients with pathological abrasion of hard dental tissues is due to the progressive development of abrasion, an increase in the free interocclusal space, a decrease in the interalveolar distance and the size of the lower part of the face. The microstructure and microelement composition of hard dental tissues reflect complex processes associated with age-related and pathological conditions in the body.